TRANSFORMASI SUPERVISI PENDIDIKAN DI INDONESIA: Kajian Sejarah, Prinsip, dan Tantangan - Hobir, Abd; Munib, Abdul (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
Educational supervision is an important component of the education system that functions not only as supervision, but also professional coaching and guidance for educators. This article discusses the development of educational supervision from the past which tended to be administrative and controlling, to a modern paradigm that is more humanistic, collaborative, and participatory. Through literature studies and related regulatory studies, the definition, objectives, functions, roles, and principles of educational supervision were explained, as well as the differences in characteristics between traditional supervision and current supervision. Modern supervision places teachers as partners in professional development, with a focus on improving the quality of learning and educational innovation, including the use of technology in e-supervision. The results of the study show that the effectiveness of supervision is highly dependent on the application of scientific, democratic, cooperative, constructive, and creative principles, as well as the active involvement of principals and supervisors. By understanding the development of supervision concepts and practices, it is hoped that educational institutions will be able to improve the quality of the teaching and learning process in a sustainable manner.